Mechanism of anti-cancer effect of β-glucan on SH-SY5Y cell line (Bangladesh Journal of Pharmacology, 2021)
Anti-cancer property of fungi derived β-glucan (Lentinula edodes) on several cancer cell lines have been reported. In this work, the SH-SY5Y cell lines were treated with various concentrations of β-glucan (62.5, 125, 250 and 500 μg/mL) and the viability of the cells was tested using the XTT assay after 24 hours. Cleaved PARP, BCL-2, 8-hydroxy-desoxyguanosine (8-oxo-dG), cleaved caspase 3, Bax, total oxidant, and total antioxidant levels in the cells were measured by commercial kits. β-Glucan significantly decreased the cell viability in SH-SY5Y cells. ELISA tests demonstrated that β-glucan therapy dramatically increased 8-oxo-dG, cleaved caspase 3, Bax, cleaved PARP, total oxidant. However, β-glucan treatment did not change the BCL-2 protein level. Altogether, β-glucan caused significant cytotoxicity in SH-SY5Y cells by inducing oxidative stress, increasing DNA damage, and ultimately increasing apoptosis.